2005
DOI: 10.1111/j.1472-765x.2005.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cold-active pectate lyases from psychrophilic Mrakia frigida

Abstract: Aims: This study was conducted to determine optimal conditions for pectate lyase (PL) production by two psychrophilic yeast strains and to compare the properties of the cold-active enzymes using mesophilic PL as reference enzyme. Methods and Results: Two psychrophilic yeasts isolated from remote geographical locations (European Alps, north Siberia) produced extracellular cold-active PL. Both strains were identified as Mrakia frigida by analysis of ITS and large subunit (LSU) rRNA sequences. Maximum enzyme prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 28 publications
4
32
0
2
Order By: Relevance
“…Assimilation of carbon and nitrogen compounds and growth requirements were tested at 10-15 uC. was examined at 1-30 uC (5 uC intervals) in liquid culture and on agar plates; pectate lyase production was determined as described previously (Margesin et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assimilation of carbon and nitrogen compounds and growth requirements were tested at 10-15 uC. was examined at 1-30 uC (5 uC intervals) in liquid culture and on agar plates; pectate lyase production was determined as described previously (Margesin et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…These enzymes could be useful for a wide range of applications, such as the food industry for juice clarification below 5 u C or low-temperature pre-treatment of wastewater containing pectic substances. Two cold-active pectate-lyaseproducing strains (Margesin et al, 2005) were previously assigned to Mrakia frigida on the basis of internal transcribed spacer (ITS) and large-subunit (LSU) rRNA gene sequences. However, detailed investigation of the strains demonstrated the absence of teliospore production, which is characteristic of the genus Mrakia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, López-Archilla et al(2004) isolated some Mrakia species from Tinto River. Margesin et al(2005) studied the cold-active pectate lyases from psychrophilic Mrakia frigida. We report here the isolation and characteristics of a psychrophilic yeast strain Y18, isolated from soil samples near the Great Wall Station of China in Fildes Peninsula, Antarctica.…”
Section: Introductionmentioning
confidence: 99%
“…SC-G and SC-H and also from two yeast strains isolated from grapes (Cabeza et al, 2009). Pectate lyase genes have been cloned and the enzyme overexpressed from the marine antarctic bacterium Pseudomonas haloplanktis strain ANT/505 was pectinolytic toward citrus pectin agar (Truong et al, 2001), with optimal activity at 30 • C and a 2-min half-life at 40 • C. The psychrophilic yeast Mrakia frigida also produces a cold-active pectate lyase with optimal activity at 30 • C (Margesin et al, 2005). Birgisson et al (2003) also found eight strains of cold-adapted yeasts, including Cryptococcus and Cytofilobasidium spp.…”
Section: Enzymes From Cold-adapted Organismsmentioning
confidence: 99%